Elucidating the Effect of Iron Doping on the Electrochemical Performance of Cobalt‐Free Lithium‐Rich Layered Cathode Materials. Issue 43 (1st October 2019) - Wu, Fanglin; Kim, Guk‐Tae; Kuenzel, Matthias; Zhang, Huang; Asenbauer, Jakob; Geiger, Dorin; Kaiser, Ute; Passerini, Stefano
Abstract: The eco‐friendly and low‐cost Co‐free Li1.2 Mn0.585 Ni0.185 Fe0.03 O2 is investigated as a positive material for Li‐ion batteries. The electrochemical performance of the 3 at% Fe‐doped material exhibits an optimal performance with a capacity and voltage retention of 70 and 95%, respectively, after 200 cycles at 1C. The effect of iron doping on the electrochemical properties of lithium‐rich layered materials is investigated by means of in situ X‐ray diffraction spectroscopy and galvanostatic intermittent titration technique during the first charge–discharge cycle while high‐resolution transmission electron microscopy is used to follow the structural and chemical change of the electrode material upon long‐term cycling. By means of these characterizations it is concluded that iron doping is a suitable approach for replacing cobalt while mitigating the voltage and capacity degradation of lithium‐rich layered materials. Finally, complete lithium‐ion cells employing Li1.2 Mn0.585 Ni0.185 Fe0.03 O2 and graphite show a specific energy of 361 Wh kg −1 at 0.1C rate and very stable performance upon cycling, retaining more than 80% of their initial capacity after 200 cycles at 1C rate. These results highlight the bright prospects of this material to meet the high energy density requirements for electric vehicles. Abstract : A comprehensive structural, morphological, and electrochemical investigation reveals the impact of iron doping on the capacity loss mechanism of cobalt‐free Li‐rich (LRNM) layered positive electrode materials. The introduction of iron reduces nickel migration into the transition metal layer and the accompanying structural transformation leading to the voltage fading of LRNM‐layered positive electrode materials.